2022
DOI: 10.1021/acs.energyfuels.2c01217
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization and Emission Characteristics of Gliding Arc-Assisted NH3/CH4/Air Premixed Flames in a Swirl Combustor

Abstract: This paper investigates the effects of gliding arc (GA) discharge on the stabilization and emission characteristics of premixed NH3/CH4/air swirl flames under various ammonia contents, flow rates, and global equivalence ratios. First, the lean blowout (LBO) limits are measured. We find that although blending CH4 extends the LBO limit of the ammonia flame to 0.6–0.8, the GA discharge further remarkably extends it to 0.3–0.4. Then, the flow and flame structures are visualized by simultaneous OH planar laser-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Ariemma et al indicated that the increased OH production due to CH 4 oxidation consumes NH 2 radicals, which inhibits the DeNO x process. To mitigate high NO x emissions from NH 3 /CH 4 combustion, various combustion technologies have been adopted, including gliding arc-assisted combustion, , rich-lean combustion, , pressurized combustion, and flameless combustion. , In many studies, a small percentage of NH 3 is adopted as the fuel-N source. , As the NH 3 proportion increases, the concentrations of OH, N, and HNO radicals are altered, thereby influencing NO x formation characteristics. Zhang et al and Filipe Ramos et al both noted that the NO x emissions reach the peak value when the volume fraction of NH 3 in the fuel ( V NH 3 ) equals 0.5.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ariemma et al indicated that the increased OH production due to CH 4 oxidation consumes NH 2 radicals, which inhibits the DeNO x process. To mitigate high NO x emissions from NH 3 /CH 4 combustion, various combustion technologies have been adopted, including gliding arc-assisted combustion, , rich-lean combustion, , pressurized combustion, and flameless combustion. , In many studies, a small percentage of NH 3 is adopted as the fuel-N source. , As the NH 3 proportion increases, the concentrations of OH, N, and HNO radicals are altered, thereby influencing NO x formation characteristics. Zhang et al and Filipe Ramos et al both noted that the NO x emissions reach the peak value when the volume fraction of NH 3 in the fuel ( V NH 3 ) equals 0.5.…”
Section: Introductionmentioning
confidence: 99%
“…Ariemma et al 36 indicated that the increased OH production due to CH 4 oxidation consumes NH 2 radicals, which inhibits the DeNO x process. To mitigate high NO x emissions from NH 3 /CH 4 combustion, various combustion technologies have been adopted, including gliding arc-assisted combustion, 37,38 rich-lean combustion, 39,40 pressurized combustion, 41 and flameless combustion. 42,43 In many studies, a small percentage of NH 3 is adopted as the fuel-N source.…”
Section: Introductionmentioning
confidence: 99%